Enhancing MSMEs’ Financial Literacy Through Cost of Goods Sold (COGS) Workshop: A Collaborative Case Study Between Bank BTN Madiun Branch and the Pendekar UMKM Bersatu Marketing Cooperative - Basuki Rahmat; Intan Puspitasari (International Journal of Economics, Science, and Education, 2025)
The Cost of Goods Sold (COGS) workshop is a strategic initiative to improve the financial literacy of Micro, Small, and Medium Enterprises (MSMEs). This article documents the implementation of a collaborative workshop between Bank BTN Madiun Branch and the Pendekar UMKM Bersatu Marketing Cooperative in Madiun City, held on May 14, 2025. The workshop was attended by 55 MSME actors from Madiun, Magetan, Ponorogo, and Ngawi. Its objective was to equip participants with practical skills in calculating production costs to set competitive selling prices and avoid business losses. This study uses a qualitative descriptive method with a case study approach. Data were collected through observation, documentation, pre- and post-tests, and brief interviews. The results indicate an improvement in participants understanding of cost structures and accurate COGS calculation practices. This collaborative training model proves effective and has the potential to be widely replicated as a financial literacy based MSME empowerment strategy.